Bilateral hydrosalpinges, what to do :Salpingectomy or salpingoplasty? Result of a 480 cases continuous series - Antoine Watrelot; Jing Guan (BMJ Publishing Group, 2021)
Background: Hydrosalpinx is the most common lesion of the distal part of the tube. Hydrosalpinx is well known to have deleterious effect on fertility. Methods: Two options are doable in case of hydrosalpinx: radical treatment(salpingectomy) or conservative treatment (salpingoneostomy). Results: This work demonstrates that in experienced hands and with an acute selection, salpingoneostomy gives results comparable to those obtained after IVF.The cuff salpingoneostomy technique is much better than racket form salpingoneostomy and should be preferred whenever it is possible. Conclusions: Conservative treatment should be discussed in infertile patients having hydrosalpinx after a careful selection.